Isolated Bone Lesions in the Mandible and Maxilla of Langerhans Cell Histiocytosis Treated with Fractionated Stereotactic Low-Dose Radiotherapy: Case Report and 5-Year Follow-Up - Antoine Berberi; Georges Aoun; Georges Aad; Elie Azar (Hindawi Limited, 2021)
Langerhans cell histiocytosis is a benign histiocytic disorder touching both genders and can occur at any age. It is currently classified by the Histiocyte Society as an inflammatory myeloid neoplasm of mixed cellularity. Clinically, it is illustrated by single or multiple osteolytic bone lesions associated with ulceration of the skin and soft tissues. Disease outcome is highly variable, depending on the degree of involvement. Bone pathologies are observed in 60% of cases as uni- or multifocal lesions. Several treatment modalities have been proposed and include surgical excision, intralesion steroid injection, chemotherapy, and low-dose radiotherapy. In this paper, we report a case of a 42-year-old male suffering from gingival swelling in the left side of his mandible and the right side of the maxilla. Clinical, radiological, and histological examinations confirm the diagnosis of Langerhans cell histiocytosis. Hematological investigation, entire body CT scan, and bone scintigraphy confirmed the limitation of the lesions in the right maxilla and on the left mandible. The lesions were treated with fractionated stereotactic low-dose radiotherapy, 24 Gy in 16 fractions, by using a linear accelerator with a custom-made rigid mask for accurate immobilization of the head with confirmed precision, which allows noninvasive approaches. Complete remission was achieved clinically and radiologically after one year, and a panoramic X-ray after 5 years confirms the bone healing process. Fractionated stereotactic low-dose RT could be adopted as an effective treatment.